Easy-to-build and affordable continuous positive airway pressure CPAP device for adult patients in low-income countries. Issue 5 (2nd May 2019) - Farré, Ramon; Montserrat, Josep M.; Solana, Gorka; Gozal, David; Navajas, Daniel
Continuous positive airway pressure (CPAP) is the treatment of choice for several types of sleep disordered breathing (SDB), of which sleep apnoea is an obvious example. Although precise epidemiological data are scarce, SDB are prevalent in low-income countries (LICs) [1, 2]. Moreover, given that the risk of SDB is associated with the patient's body mass index, and that the worldwide obesity pandemic involves not only developed countries but also LICs [2, 3], it is expected that the incidence of sleep apnoea will continuously increase in LICs, and the need for CPAP devices will accordingly rise. Moreover, the demand for CPAP devices in LICs is also anticipated to increase in light of the few operationally equipped intensive care units in these countries [4]. Indeed, cheap CPAP devices, although with less versatile applications than mechanical ventilators, provide rescue and treatment options that can reduce mortality and intubation rates in some patients [5]. Unfortunately, these options are seldom implemented in LICs since neither patients nor hospitals are able to afford commercial CPAP devices. It is also noteworthy that CPAP devices specifically designed and commercialised in LICs [6], which achieve cost reductions by avoiding optional device features [7], do not offer a realistic therapeutic alternative. Teams from developed and developing countries have collaborated to design and test a low-cost, high-performance device to apply continuous positive airway pressure for treating patients in low-income countries http://ow.ly/Cllj30nMGQq